IMPACTS OF PENSION REFORMS ON THE KENYAN PENSION INDUSTRY - Victoria, Masinde Mercy; Olukuru, John L (European Scientific Journal, ESJ, 2015)
The emergence of full-fledged reforms in Kenya from the introduction of the Retirement Benefits Authority in 1997 has rekindled hopes among the ageing population in Kenya. This paper examines the effect of the NSSF Act 2013 contribution rate by use of a contribution rate model as well as Kenyans’ perception towards the yet to be implemented Act by use of questionnaire analysis. The study asserts that the set 6% is sufficient to meet the welfare conditions of Kenyans. Further, this study also identifies the main social welfare reforms put in place, as well as the effects and challenges towards implementation of the reforms on the performance of the industry with a critical theoretical look at the NSSF Act 2013.